ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI GABAH PETANI DI SUBAK GEDE YEH NU DESA GUBUG KECAMATAN TABANAN KABUPATEN TABANAN - I DEWA GEDE RASTANA; I WAYAN MULA SARJANA (Universitas Mahasaraswati K. Mataram, 2022)
Tabanan Regency is one of the regencies/cities in Bali Province which has great potential in the agricultural sector. The area of agricultural land in Subak Gede Yeh Nu, Gubug Village, Tabanan District, Tabanan Regency as a whole was recorded at 598 (Ha). Where it is divided into three subaks, namely: Subak Gubug I the land area is recorded at 189 (Ha) or 31.61% of the total land area, the land area for Subak Gubug II is recorded at 255 (Ha) or 42.64% of the total area. land as a whole. The land area for Subak Gubug III is 154 (Ha) or 25.75% of the total land area. The phenomenon of land area in Subak Gede Yeh Nu, Gubug Village, Tabanan District, Tabanan Regency, is the amount of agricultural land that is converted to the housing sector (property) which has an impact on the land area which is getting narrower every year.The purpose of the study was to determine the effect of capital, labor, and land area on the rice production of farmers in Subak Gede Yeh Nu, Gubug Village, Tabanan District, either partially or simultaneously. Sampling in this study was carried out using the Proportionate Stratified Random Sampling technique, as many as 95 farmers in Subak Gede Yeh Nu, Gubug Village, Tabanan District. The data analysis technique used multiple linear regression analysis.The results showed that capital, labor, and land area partially had a significant and positive effect on farmers' grain production in Subak Gede Yeh Nu, Gubug Village, Tabanan District. Furthermore, capital, labor, and land area simultaneously significantly affect the grain production of farmers in Subak Gede Yeh Nu, Gubug Village, Tabanan District, with F count 169.15 > F table 2.705.